Mothers’ perception of the use of non-pharmacological methods for pain relief in nurslings (Research, Society and Development, 2021)
The objective of the study was to comprehend the perceptions parents possess in relation to pain management during their child’s vaccination, in a private vaccination clinic in the city of Florianópolis. This is a research with a qualitative approach, through Grounded Theory. Data were collected from 10 mothers from June to August 2019, through semi-structured, recorded and individual interviews in a private immunization clinic located in the city of Florianópolis / SC. Three categories emerged as results that foster the central phenomenon of the research “Mothers’ perception when using breastfeeding as a non-pharmacological method for pain relief in children undergoing vaccination”. Through this study, we can identify those non-pharmacological methods for pain relief, as much as they reverberate in the increase of satisfaction and in the decrease of maternal distress during this moment, are still underused in clinical practice. It concludes that such methods still are rarely studied, despite having great value for the relief of pain and trauma for nurslings and their respective parents and/or caregivers. The nurse's importance, in the context of vaccination, should be valued since its practical theoretical knowledge is fundamental pieces for the success in the management of pain.